Election Security and Women Political Participation in Nigerian Democratic System 1999-2023 - Zango, AbdulAziz Sani (Kashere Journal of Politics and International Relations, 2024)
The transition to democracy has been marked with strenuous attempt and sacrifices that have left indelible marks that could remember for a very longer time in the political history of Nigeria. This may not be unconnected with hope and aspirations that greeted the project, how ever, a few years into democratic practice these hope and aspirations dashed out to such an extent that for the past two decades the Nigerian Democratic practices has been continuously declining in such an alarming rate that even the highest manifestation of democracy in term of election is waning thus can be seen from the trend of serious decline in voters attitudes towards registration and voting as well as in political activities in general. A survey of the trend successively reveals the clear picture from 2003 to 2023 where it is gloomier. This automatically has a very serious negative implication on democracy in general in the country. This paper ssesses the level of women's political participation under the current democratic dispensation in Nigeria; and it also examines the ways elections security affects women political participation in Nigeria; and examine factors that shapes and influences women political participation both as electorates and candidates in Nigeria